Role improvising during crisis situations. (21st September 2004) - Webb, Gary
This research describes the various ways key responders improvise their disaster-related roles during the emergency period of large-scale crises. Using archival data from the University of Delaware's Disaster Research Center in the USA, this paper presents an empirically-derived classification of role improvisations occurring in natural disasters, technological crises, and civil disturbances. Five types of role improvising are identified: procedural changes, status changes, normative-order changes, equipment changes, and location/facility changes. The paper concludes by discussing the implications of the classification scheme for the practice of emergency management and for future studies of role improvising in both routine and non-routine social settings.